2014
DOI: 10.1177/1076029614546328
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban Versus Enoxaparin in Elective Major Orthopedic Surgery

Abstract: Despite current guidelines recommendations about anticoagulant prophylaxis, many studies have shown an high venous thromboembolism (VTE) incidence in patients undergoing total hip and knee arthroplasty. A number of anticoagulants are currently available, but they have some limitations that affect their applicability and consequently their effectiveness. Several new oral anticoagulants (NOACs) have been developed in an attempt to overcome these limitations. Apixaban is a NOAC that selectively inhibits the coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…When compared individually for TKA and THA, apixaban was found to be associated with significantly lower risk of having an adverse event in the THA group while this was not significant in the TKA group. This finding is consistent with previous trials and meta‐analyses, which have showed that either apixaban is safer than enoxaparin or there is no significant difference between the 2 when compared for safety profiles 7–13,22–25 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When compared individually for TKA and THA, apixaban was found to be associated with significantly lower risk of having an adverse event in the THA group while this was not significant in the TKA group. This finding is consistent with previous trials and meta‐analyses, which have showed that either apixaban is safer than enoxaparin or there is no significant difference between the 2 when compared for safety profiles 7–13,22–25 …”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with previous trials and meta-analyses, which have showed that either apixaban is safer than enoxaparin or there is no significant difference between the 2 when compared for safety profiles. [7][8][9][10][11][12][13][22][23][24][25] This study shows no significant difference between incidences of VTE with the sex of patient similar to conclusion drawn by Schiff et al, although age showed a significant correlation with VTE irrespective of the group, similar to data reported earlier. 26 No study has previously reported the comparison of enoxaparin and apixaban with functional outcome of an arthroplasty patient.…”
Section: Safety Outcomesupporting
confidence: 92%
“…14 Despite these recommendations, recent studies show the superiority of rivaroxaban and other NOACs in preventing VTE, without increasing major bleeding or all-cause mortality, compared with enoxaparin. [16][17][18][19] Furthermore, even more recently, the ICM-VTE: Hip & Knee recommendations state aspirin as the most effective and safest choice. 15 In our analysis, we found out that women compose the vast majority of the patients undergoing TKR (77.66%) in this hospital (Table 1), so one might point out that the incidence of knee osteoarthritis might be bigger in women.…”
Section: Discussionmentioning
confidence: 99%
“…14 Despite these recommendations, recent studies show the superiority of rivaroxaban and other NOACs in preventing VTE, without increasing major bleeding or all-cause mortality, compared with enoxaparin. 16-19 Furthermore, even more recently, the ICM-VTE: Hip & Knee recommendations state aspirin as the most effective and safest choice. 15…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, the major orthopedic surgery can result in the high risk for venous thromboembolism, which can potentially lead to various chronic complications. Therefore, the DVT prophylaxis has been the conventional care for patients who ever undergo major orthopedic surgery in clinical practice [ 25 , 26 ]. At present, a variety of treatment to prevent DVT are necessary and available in clinical practice, and the two primary approaches are pharmacological strategy and mechanical devices, such as antiplatelet, anticoagulant, IPCD, graduated compression stockings, and plantar vein pumps, etc.…”
Section: Discussionmentioning
confidence: 99%